Ocena chemizmu gleb powstałych na bazie popiołów z węgla kamiennego po dziesięciu latach ich funkcjonowania w środowisku = The assesment of chemical properties of soils made on base of ashes from hard coal after ten years of their functioning in environment - Tomaszewicz, Tomasz; Chudecka, Justyna (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of study was to evaluate chemical properties of 10-year-old soils made by submission on ashes from hard coal 5 variants of surface layer including organic matter of natural and anthropogenic origin.
Keywords: popioły z węgla kamiennego; rekultywacja; gleby antropogeniczne; właściwości chemiczne; ashes from hard coal; reclamation; anthropogenic soils; chemical properties